ORTHOTOPIC LIVER TRANSPLANTATION: ROLE OF INTERVENTIONAL RADIOLOGY - P. G. Tarazov; D. A. Granov; A. A. Polikarpov; M. I. Generalov; F. K. Zherebtsov; O. A. Krotova; O. A. Gerasimova; D. N. Maystrenko; A. V. Kozlov; I. O. Rutkin (Вестник трансплантологии и искусственных органов)
To study therapeutic modalities of interventional radiology in patients (pts) before and after orthotopic liver trans- plantation (OLT). OLT was performed in 53 pts between 1998 and 2008. Endovascular treatments were performed in 20 pts. Pre-OLT interventional procedures included transcatheter arterial chemoembolization (5 patients) and TIPS (8 patients). Post-OLT procedures were: dilatation or/and stenting of biliary strictures (4), stenting of IVC (2), balloon dilatation of cava-caval anastomosis (1), partial splenic embolization (PSE) in steel syndrome (1). All IR procedures were technically successful. There was no mortality or serious complication. After chemoemboliza- tion, there was partial tumor response in all 5 patients with HCC; two successfully transplanted are alive without recurrence in 11 and 15 months. After TIPS, 3 pts underwent OLT. Satisfactory biliary passage was achieved in all pts with strictures. Clinical symptoms and liver function improved in three pts with venous strictures. After PSE, steal syndrome regressed rapidly. All pts are asymptomatic and well in 5–24 mo after IR treatment. IR procedures prolong long-term patient survival before OLT and may improve outcomes in pts after OLT.